METODE PENAFSIRAN AL-QURAN - Yusuf, Muhammad Yunan (SYAMIL, 2014)
The Quran was revealed in Arabic. In understanding the Quran, for the people who use the Arabic language and the people who do not use Arabic language needs specific competence. Without the competence, people will not be able to capture the content and message of the Quran correctly. The specific competence is interpretation/tafsir. Tafsir has thariqah at-tafsir, a method or a way of interpreting the Quran. Errors in understanding Quran will also cause errors in delivering the teaching Quran. The interpretationsâ clerics explain that in interpreting the Quran, there are four methods: 1) tahlili method, 2) ijmali method, 3) comparison method and 4) thematic method.